USE OF MEDIA NALAR GAME IN TRAINING SKILL MULTIPLICATION ON DEAF STUDENTS IN PRIMARY SCHOOL X BANDUNG DISTRICT - Djuang Fitriani (PrimaryEdu : Journal of Primary Education, 2019)
The presence of inclusive education needs more attention. Especially in basic education. In the process of learning in children with hearing impairment is the most important thing in the success of learning that is; 1) teacher-student affairs, 2) information legibility and, 3) the appropriate type of tools to clarify the subject matter. Researchers try to use the media game reasoning that if it can help solving in the practice of multiplication skills. It can also be done in the form of a game, helping students psychologically to learn, possessing appeal as if playing but essentially learning, thus increasing the success of learning deaf children in math skills. The research used is action research school (PTK). The result of learning of deaf students with media of game reasoning on learning mathematics of mathematics conception happened improvement of significant learning result from pre test result with post test, this proves that game reasoning media can improve learning result in mathematics learning mathematics concept in class 4 Elementary School X Regency BandungKeywords: Inclusive education, Basic education, Deaf Children, Game reasoning, Multiplication Skill.